Lamin A safeguards the m6A methylase METTL14 nuclear speckle reservoir to prevent cellular senescence. Issue 10 (19th August 2020) - Zhang, Jie; Ao, Ying; Zhang, Zhen; Mo, Yanzhen; Peng, Linyuan; Jiang, Yue; Wang, Zimei; Liu, Baohua
Abstract: Mutations in LMNA gene are frequently identified in patients suffering from a genetic disorder known as Hutchison–Gilford progeria syndrome (HGPS), providing an ideal model for the understanding of the mechanisms of aging. Lamin A, encoded by LMNA, is an essential component of the subnuclear domain‒nuclear speckles; however, the functional significance in aging is unclear. Here, we show that Lamin A interacts with the m 6 A methyltransferases, METTL3 and METTL14 in nuclear speckles. Lamin A deficiency compromises the nuclear speckle METTL3/14 reservoir and renders these methylases susceptible to proteasome‐mediated degradation. Moreover, METTL3/14 levels progressively decline in cells undergoing replicative senescence. Overexpression of METTL14 attenuates both replicative senescence and premature senescence. The data reveal an essential role for Lamin A in safeguarding the nuclear speckle reservoir of the m 6 A methylase METTL14 to antagonize cellular senescence. Abstract : Lamin A interacts with the m 6 A methylase METTL14 to ensure the proper localization in the nuclear speckles and protein stability. METTL14 declines in senescent cells, while its overexpression antagonizes cellular senescence.